Determination the Concentration Elements of Cultivation Media (Peat Moss, Perlite and Hormone) Using X-ray Fluorescence Technique - Al Saedi, Jamal K.; Alalawy, Ramla D.; Hasan, Nada M. (Iraqi Journal of Science, 2018)
The concentration of elements were analyzed of twelve cultivation medium (Peat moss, Perlite and Hermon) selected from Iraqi markets using X-ray fluorescence techniques. The analytical results show that the cultivation medium contained high concentration of (Na, Al, Si, S, K, Ca, Fe) and low concentration of (Mg, P, Cl, Ti, V, Cr, Mn, Co, Ni, Cu, Zn). The samples also contained trace concentration of (Ge, As, Se, Br, Sr, Y, Mo, Cd, I, Hg, Pb, U). The results were compared using atomic absorption spectrophotometric technique for measuring the concentration of (K, Ca, Cu, Mn, Zn, Pb). The Results showed that there is significant difference in the concentration of each element in most of the samples. The concentrations of elements are in threshold levels except few elements such as aluminum. The Cd concentration was higher than the limit in some samples. To purpose of evaluating the precision of the analysis results, calculated the standard deviation SD and relative standard deviation, it was found in the range of (0.004561-0.328634) %, (1.09-19.23) % and accuracy was found in the range of (0.27-44.32) %.